Odpowiedzi

  • Użytkownik Zadane
2010-03-16T15:31:38+01:00
A) 2x (x -1) = 2x² + 4
2x²-2x = 2x² + 4
-2x=4 /:-2
x=-2

b) 1/2x (4- 6x) - 1/3x (9x-12)= - 2 x(3x+1)
2x-3x-3x+4x = -6x² -2x
-6x² -2x=0
-2x(3x+1)=0
x=0 lub x=-1/3

c)(y- 2)(3+2y) - y2= y2+5
3y+2y²-6-4y-y²=y²+5
-y=11
y=-11

d) x(x-2) - 2x(x+1)= -5x2-3
x²-2x -2x²-2x = -5x²-3
-x²-4x+5x²+3=0
4x²-4x+3=0
Δ= 16-48
Δ<0 (brak rozwiązań)
  • Użytkownik Zadane
2010-03-16T15:42:28+01:00
A)2x-2x=4x + 4
2x-2x-4x=4
-4x=4//:(-4)
x=-1
b)2x-3x-2,7x+3,6x=-2+3x+x
2x-3x-2,7x+3,6x+3x+x=-2
4,1x=-2//:4,1
x=-0,48
c)y-2*3+2y-2y=2y+5
y+2y-2y-2y=6+5
-y=11
y=11
d)x-2x-2x-2x=-5*-1
-5x=5//:(-5)
x=-1